2017
DOI: 10.1007/jhep11(2017)180
|View full text |Cite
|
Sign up to set email alerts
|

SYK model, chaos and conserved charge

Abstract: Abstract:We study the SYK model with complex fermions, in the presence of an all-toall q-body interaction, with a non-vanishing chemical potential. We find that, in the large q limit, this model can be solved exactly and the corresponding Lyapunov exponent can be obtained semi-analytically. The resulting Lyapunov exponent is a sensitive function of the chemical potential µ. Even when the coupling J, which corresponds to the disorder averaged values of the all to all fermion interaction, is large, values of µ w… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
43
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 38 publications
(46 citation statements)
references
References 46 publications
2
43
0
1
Order By: Relevance
“…In our case the full suppression occurs only at the infinite µ in contrast to the full suppression in the complex fermions SYK model appeared at finite value of µ. This may be related with the large q approximation used in [6].…”
Section: Discussion and Connection With Syk-like Modelsmentioning
confidence: 55%
See 1 more Smart Citation
“…In our case the full suppression occurs only at the infinite µ in contrast to the full suppression in the complex fermions SYK model appeared at finite value of µ. This may be related with the large q approximation used in [6].…”
Section: Discussion and Connection With Syk-like Modelsmentioning
confidence: 55%
“…In [6] it was shown, that in the SYK model with the complex fermions introduction of the chemical potential lead to the effect of chaos damping. There is a little difference with our results.…”
Section: Discussion and Connection With Syk-like Modelsmentioning
confidence: 99%
“…are associated with x ± respectively. of a chemical potential [21]. Here the Lypunov index computed was found to be bounded by 2π/β.…”
Section: Resultsmentioning
confidence: 81%
“…Indeed, some studies addressing the connection between the RMT properties of SYK and the OTOCs appeared in recent days: very recently, [58] has studied the onset of RMT behavior in the (Gaussian filtered) SYK SFF 6 and found that, in agreement with the results of [59], the time-scale at which the RMT behavior appears -which we will call Thouless time -is not the 4 Indeed, a priori there could be systems which are chaotic according to one definition and not chaotic according to the other. 5 For example, see the U (1) symmetry and flavor generalizations [16][17][18][19][20][21], supersymmetric generalizations [22][23][24][25][26][27], SYK(-like) models without disorder [28][29][30][31][32][33][34][35][36][37][38][39][40][41][42][43], gravity duals [44][45][46][47][48][49][50][51] and the Schwarzian theory [52][53][54]. 6 As we will revi...…”
Section: Introductionmentioning
confidence: 99%